Evaluation of Group B Streptococcus culture processing using a commercial flocked swab with and without automated sample processing instrument - Richard D. Smith; Paul M. Luethy; J. Kristie Johnson (Microbiology Spectrum)
ABSTRACT Group B Streptococcus (GBS) is the most common cause of neonatal sepsis. Screening for vaginal-rectal colonization of the mother is important to prevent exposure. The current standard diagnostic method for GBS is to collect a vaginal-rectal swab and inoculate in LIM broth to increase sensitivity. Use of flocked swabs such as Eswabs has become the recommended collection device due to their increased recovery rates and potential for automation. Despite being the recommended collection device, there is a lack of adequate literature providing guidance on processing of Eswabs for GBS cultures. This study sought to address this by investigating the optimal volume of transport media to inoculate in LIM broth, determining the limit of detection using the Copan WASP automated laboratory processor, and evaluating the accuracy of the WASP for recovering GBS using Eswabs. This study found that GBS can be recovered at multiple inoculation volumes except at 10 µL at a bacterial concentration of 10° CFU/mL, where it had a recovery rate of 80% (12/15). Moreover, when inoculating in LIM broth, the limit of detection for GBS using the WASP was 100% at 101 CFU/mL. When using clinical specimens, WASP had 100% sensitivity and specificity. Overall, this study demonstrated that the WASP is an excellent automated method for processing GBS swabs. For laboratories without automation, this study demonstrates that any volume greater than 10 µL can recover GBS at a concentration greater than 100 at 100% recovery rate compared to the gold standard of manual inoculation and plating.IMPORTANCEDespite several published guidelines on how to process Group B Streptococcus (GBS), including type of swabs, media, incubation, and other molecular technology, there are no clear guidelines regarding the ideal volume of transport media to inoculate into LIM broth. Thus, this study investigated using manual and automated processing techniques. Moreover, as automation becomes a critical part of laboratory science, this study addresses and evaluates the use of automation for GBS.